PENGARUH MEDIA FILM ANIMASI NUSSA DAN RARRA TERHADAP PENDIDIKAN KARAKTER SISWA - Suci Dwi Lestari; Abdul Khoir HS (Turats, 2022)
Many moral declines occur, one of which is in the world of education, one of which is the use of smartphones in school children where they are easily influenced by trend developments through social media. So parents have to be extra in educating their children at home. In addition, the decline in ethics and morals that is happening at this time makes schools also strive to educate in order to realize the character education achieved. The government launched Strengthening Character Education (PPK) which can be integrated into the educational curriculum, one of which is through learning activities in schools using sophisticated and effective media. Researchers used the animated film Nussa and Rarra as a tool in the study. So this study aims to determine the effect of the animated film Nussa and Rarra on the character of students in PAI learning class IV SDN Karangsetia 03 Kab. Bekasi. This research is a quantitative research with the type of research design quasi experiment. With a population of all fourth grade students at SDN Karangsetia 03, the samples used were grades IV A and IV C. The data collection techniques used in this study were questionnaires and tests. The results obtained After being given treatment (treatment) and conducted a posttest. Character education of students is better using the animated film Nussa and Rarra compared to learning using power point media because it is more effective and varied, this is reinforced by the results of statistical tests assisted by SPPS version 25. The animated film media Nussa and Rarra has an effect on students' character education because the animated film Nussa and Rarra is not only funny but contains character education values ​​in each episode, then the role of the character has the potential to be imitated by children or become role models and this animated film contains a religious theme that is thick with the adab and behavior of a Muslim. The results of the attitude assessment must be understood as a process not as the result of an instant learning process that is assessed by educators every time they complete the learning process. Therefore, this assessment is an accumulative process or will continue to develop on student behavior indefinitely.